PELAKSANAAN STANDAR OPERASIONAL PROSEDUR PEMBERSIHAN KAMAR TAMU DENGAN PROTOKOL KESEHATAN DI ARDAN HOTEL BANDUNG - Superwiratni; Mega Amalia (Akademi Pariwisata NHI Bandung, 2021)
The spread of the coronavirus outbreak that is so fast today in Indonesia has a great influence on the economy of the community is no exception also has an impact in the world of tourism and hotels in particular. Physical distancing, wearing masks, washing hands, using hand sanitizer and implementing health protocols based on CHSE are applied in hotels so as to change the Standards of Oprasional Cleaning Procedures in hotel areas including rooms. As Sailendra (2015:11) said